2011
DOI: 10.1037/a0024197
|View full text |Cite
|
Sign up to set email alerts
|

Counseling psychology in clinical health psychology: The impact of specialty perspective.

Abstract: Not all clinical health psychologists are trained as clinical psychologists. A significant minority is trained and identifies as counseling psychologists. As a field, it is important to understand how the specialtyspecific values, training context, scholarship, and parameters of practice of counseling psychology contribute to clinical health psychology. In this article, we (a) identify the core values and training context of counseling psychology, (b) review the scholarly history of clinical health psychology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Although counseling psychologists focus primarily on objective personality assessment (see “Petition for the Recognition of a Specialty in Professional Psychology” [Lichtenberg et al, 2012]), they are attuned to the historical and social significance of projective measures. Training programs integrate developments in health service psychology (i.e., health-related measures), and attend to developments regarding the frequency of administering specific assessments, measures, and evaluations in professional practice (Nicholas & Stern, 2011). Additionally, counseling psychology has a unique history of practice in the field of vocational guidance and assessment (see Delgado-Romero et al, 2012, for a review of the specialty’s involvement).…”
Section: Characteristics Of a Model Counseling Psychology Doctoral Prmentioning
confidence: 99%
“…Although counseling psychologists focus primarily on objective personality assessment (see “Petition for the Recognition of a Specialty in Professional Psychology” [Lichtenberg et al, 2012]), they are attuned to the historical and social significance of projective measures. Training programs integrate developments in health service psychology (i.e., health-related measures), and attend to developments regarding the frequency of administering specific assessments, measures, and evaluations in professional practice (Nicholas & Stern, 2011). Additionally, counseling psychology has a unique history of practice in the field of vocational guidance and assessment (see Delgado-Romero et al, 2012, for a review of the specialty’s involvement).…”
Section: Characteristics Of a Model Counseling Psychology Doctoral Prmentioning
confidence: 99%
“…According to Nicholas (2010), approximately 12% of APA-accredited doctoral programs in counseling psychology offer clinical health psychology coursework or practicum training (as cited in Nicholas & Stern, 2011). According to Nicholas (2010), approximately 12% of APA-accredited doctoral programs in counseling psychology offer clinical health psychology coursework or practicum training (as cited in Nicholas & Stern, 2011).…”
mentioning
confidence: 99%
“…6% in 19956% in -19966% in to 9.0% in 20046% in -20056% in (CCPTP, 2005. With regard to research, a survey of 53 of the 66 APA-accredited doctoral programs in counseling psychology revealed that 68% of the programs' online websites described faculty research involvement in health psychology (Nicholas, 2010, as cited in Nicholas & Stern, 2011). With regard to research, a survey of 53 of the 66 APA-accredited doctoral programs in counseling psychology revealed that 68% of the programs' online websites described faculty research involvement in health psychology (Nicholas, 2010, as cited in Nicholas & Stern, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations